Assignment of Arterial Hypertension with Angiographic Indicators in Progressive Angina Pectoris - Marufovich, Shodiyev Mirshodbek (American Journal of Bioscience and Clinical Integrity, 2024)
To study the state of coronary angiography (CAG) in relation to the presence or absence of arterial hypertension (AH) in unstable progressive angina pectoris (UPA). Material and methods: A total of 75 patients with PHF were examined, the average age of which was 59.3±8.6 years. The ratio of men and women was 53/22, respectively. All patients underwent percutaneous coronary intervention (PCI) with stenting of the coronary arteries. Of all the examined patients, hypertension was present in 90.7% of cases. Three groups were identified: Group 1 - 9.3% of patients without hypertension; Group 2 - 57.3% of patients with hypertension of varying severity and Group 3 - 33.4% of patients with a combination of hypertension and diabetes mellitus (DM), i.e. 90.7% of PHF patients were characterized by the presence of hypertension of varying severity.